Chronic Expanding Hematomas That Occurred 20 Years or More After Primary Total Hip Arthroplasty: A Report of 2 Cases. Issue 1 (January 2021) - Ishikawa, Tomomi; Kawai, Toshiyuki; Goda, Naoki; Goto, Koji; Kuroda, Yutaka; Matsuda, Shuichi
Abstract : Case: We report 2 patients who developed chronic expanding hematomas (CEHs) more than 20 years after ceramic-on-polyethylene total hip arthroplasty (THA). One CEH occurred after a minor fall, and the other appeared with no obvious injury. Neither of the 2 was on anticoagulation. Each caused extensive osteolysis. Conclusion: The only 2 previously reported post-THA cases of CEH involved metal-on-metal THAs and occurred several years after the index THA. Our patients show that CEH also can occur after ceramic-on-polyethylene THA, even after an uneventful clinical course of more than 20 years. Complete removal of both hematoma stopped osteolytic progression, with no recurrence to date.